Mrs Birkbeck's Album: The Hand-written and the Printed in Early Nineteenth-Century Feminine Culture - Patrizia Di Bello (19, 2005)
Mrs Birkbeck's Album, collected between 1825 and 1847 by the wife of the founder of the College, contains poems, songs and other texts, as well as drawings and watercolours by famous women and men of her time. Like the collections that aristocratic women were able to spread over galleries and libraries, the album formed and displayed her taste, showcasing her husband's reputation and the cultural and political circles in which the couple moved. Several contributors to her album also worked for annuals, fashionable publications associated with a debased, commercialised feminine culture. Unlike these mechanically produced pages, Mrs Birkbeck's album, marked by individual hands rather than by printing presses, is the result of gift exchanges, removed from the world of commodified culture, even as it partakes of its glamour. Recent publications have explored the emergence of women's magazines, but little consideration has been given to album making. In this paper I explore the social meanings of Mrs Birkbeck's interest in albums. To facilitate a close reading of its individual pages, I am working towards digitising the album, in collaboration with Birkbeck Library and the Vasari Lab in the School of History of Art, Film and Visual Media.